The use of artificial intelligence in history teaching in pre-university education: pedagogical opportunities, risks, and guidelines for responsible implementation - Mehmeti, Ndriçim (Optime, 2025)
The integration of Artificial Intelligence (AI), particularly generative models (e.g., chatbots and text/ image/audio generators), is transforming the ways in which students search for information, write, interpret sources, and construct arguments. In the field of history, AI creates opportunities for per - sonalized learning, modeling of historical thinking, comparative source analysis, and didactic simu- lations; at the same time, it introduces significant risks, including factual “hallucinations,” fabricated citations, content bias, erosion of academic integrity, and the collection of minors’ personal data. This article examines the main uses of AI in history teaching in pre-university education, proposes a practical framework for implementation (planning–implementation–evaluation), and offers ready-to- use classroom scenarios. The discussion is grounded in international guidelines and in disciplinary principles of historical education such as source criticism, contextualization, and multiperspectivity. Ultimately, the article recommends a “limited-partner AI” approach, in which the teacher retains ped- agogical authority and students are trained in verification, argumentation, and transparency in their use of AI.